Rapid evidence profile #29: What do we know from evidence and experiences from other jurisdictions about providing palliative care for those who are experiencing or at risk of homelessness? - Bhuiya, AR; Bain, T; Al-Khateeb, S; Soueidan, S; Wang, A; Jarvis, T; Sood, T; Mehta, V; Wilson, MG (My University, 2022)
An overview of the best available research evidence from around the world (i.e., evidence syntheses) and local research evidence (i.e., single studies) and may include a scan of experiences from other countries and from Canadian provinces and territories, about what we know from evidence and experiences from other jurisdictions about providing palliative care for those who are experiencing or at risk of homelessness in response to a decision-maker’s request.
Keywords: experiences; palliative care; homelessness